At the Dawn of Modernity : Biology, Culture, and Material Life in Europe after the Year 1000 - Levine, David, 1946- (Book collections on Project MUSE., 2001)
This examination of the social history of modernization investigates the centuries that followed the year 1000, when a new kind of society emerged in Europe. The text highlights both the 'top-down' and 'bottom-up' changes that characterized the social experience of early modernization.